REGULATION OF MITHOCHONDRIAL GLUTAMINASE ACTIVITY IN PARAMECIUM MULTIMICRONUCLEATUM AND YEASTS $CANDIDA~GUILLIERMONDII$ NP-4 (Proceedings of the YSU B: Chemical and Biological Sciences, 2004)
The activity of enzyme glutaminaze has been investigated in the mithocondreal fraction of yeasts Candida guillermondii and parameciums Paramecium multimicronucleatum. The investigations show that phospate, bicarbonate, ATP and GTP positively can increase the activity of mithochondrial enzimes of both objects. Activating effect have some aminoacids as glicine, methionine, histidine and N-acetil triptofhane. The glutamic and aspargic acids decrease the glutaminase activity of both objects. It is also shown the modulating effect of different hormones on mithochondrial glutaminase of yeasts and parameciums as tiroxine, adrenaline, hidrocortizone. Serotonin and dexametazone show different effects on yeasts and parameciums. Both of them positively regulate the parameciums mithochondrial glutaminase, while inhibiting the yeasts glutaminase.
Keywords: enzyme glutaminaze; aminoacids; serotonin; dexametazone; mithochondrial enzimes